2017
DOI: 10.1108/ijbpa-03-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the developments in building adaptability

Abstract: This paper provides a critical review of developments in the adaptability of buildings. Its purpose is to determine the current ‘state-of-the-art’, describe current thinking and trends in research and practice, and identify issues and gaps that further research can address. It provides a basis for a scientific and practical understanding of the interdependencies across different design criterion. The paper increases the awareness of architects, engineers, clients and users on the importance of adaptability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 49 publications
0
76
0
1
Order By: Relevance
“…There are now two possibilities, modifying the building so it becomes relevant again, or tearing it down. Design for Adaptability focuses on making this modification easier by incorporating the capacity to change the building layout, encouraging the choice of modification instead of tearing down the building, and thereby aiming at longer life [89,96,[100][101][102][103][104] with the additional aim of reducing material consumption and waste from building renovation and refurbishment. An adaptable building should be designed so there is room for the function and context (economic, social, legal and political) of the building to change and adjustments can be made with ease [96,102].…”
Section: Design For Adaptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…There are now two possibilities, modifying the building so it becomes relevant again, or tearing it down. Design for Adaptability focuses on making this modification easier by incorporating the capacity to change the building layout, encouraging the choice of modification instead of tearing down the building, and thereby aiming at longer life [89,96,[100][101][102][103][104] with the additional aim of reducing material consumption and waste from building renovation and refurbishment. An adaptable building should be designed so there is room for the function and context (economic, social, legal and political) of the building to change and adjustments can be made with ease [96,102].…”
Section: Design For Adaptabilitymentioning
confidence: 99%
“…Design for Adaptability focuses on making this modification easier by incorporating the capacity to change the building layout, encouraging the choice of modification instead of tearing down the building, and thereby aiming at longer life [89,96,[100][101][102][103][104] with the additional aim of reducing material consumption and waste from building renovation and refurbishment. An adaptable building should be designed so there is room for the function and context (economic, social, legal and political) of the building to change and adjustments can be made with ease [96,102]. A building can be made adaptable through initiatives such as dividing building elements into layers so these can be adapted with minimal damage to the other layers, through designing a building without a specific use in mind, through using interchangeable components, and though designing for disassembly (see Section 5.2.6) [103].…”
Section: Design For Adaptabilitymentioning
confidence: 99%
“…This argument was illustrated by Schmidt III and Austin [11] (p. 57): their analysis of the interconnectivity of Brand's shearing layers of change [9] (i.e. Site, Structure, Skin, Services, Space Plan, and Stuff, extended to include Social, Space, and Surroundings) demonstrated that the Space Plan layer has both the highest number of links to other layers and the highest link strengths-see also: [5] (p. 289).…”
Section: Premise: Permeable Plan Layouts Are More Generalmentioning
confidence: 99%
“…However, although designing buildings for adaptability (or flexibility) has been 'a legitimate goal of architecture and planning' since the 1960s [4] (p. 51), it has arguably remained a niche field of study in architecture and building research. In a review paper discussing developments in building adaptability between 1990 and 2017, Heidrich et al [5] (p. 296) discussed the lack of methods to score and evaluate adaptability, and emphasised the need to develop approaches and tools to inform design for adaptability. Geraedts et al [6] (p. 1054) argued that existing adaptability assessment methods often only evaluate specific aspects of adaptability, such as technical or functional aspects, or focus on particular building types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation